Pelanggaran Kampanye Pemilihan Umum Perspektif Fikih Jinâyah - Farid Maulana Ramadhani (Prodi Siyasah (Hukum Tata Negara) Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2015)
Abstract: This study highlights the Islamic political jurisprudenceâ€™s against violations of the general election campaign. The violations of the campaign com Islamic political jurisprudenceâ€™s perspective mitted by the perpetrators to elect the members of DPR and DPD is something that is familiar to the public. It means that there have so often a violation of the campaign during the legislative election campaign. Although the campaignâ€™s provisions in Law No. 8 year 2012 on General Election has been set on the prohibition of the campaign and the implementation of a safe election campaign. The campaigners look like clossingÂ their eyes on the rules of the campaign. So that, it is quite difficult to be followed up by the authorities and the perpetrators are so easy to perform the prohibited action. Based on the Islamic political jurisprudenceâ€™s perspective, the election campaign violations committed by the perpetrators have some negative effects that harm and disturb the public order. So that the perpetrators can be sentenced by an educative punishment for a criminal offense that has not been determined by the shariâ€™ah. Keywords: Abuse, campaign, general election, Islamic political jurisprudence.